Impact of Integration of Medical Education in the Health System of Islamic Republic of Iran - Fereidoon Azizi; Abbass Entezari; Nader Momtazmanesh; Masoud Pezeshkian; Narges Tabrizchi (Strides in Development of Medical Education)
Background: Following the Iranian Islamic revolution in 1979, two major reforms were implemented in the nationwide health system: Establishment of the Ministry of Health and Medical Education and the development of Primary Health Care Networks. The aim of this article is to review the impact of integration of medical education in the health system.Methods: We review here the birth and growth of the integration of the health care system and medical education, the successes, the aspirations and some of the obstacles and challenges found along this path, as well as the vision and strategies for the future. All articles on this issue published in international Journal and in Iranian medical Journals were reviewed.Results: Health care and medical education in the I.R. Iran have undergone profound reform in the last four decades after integration of the Ministry of Health and all related schools and institutions of medical education. The newly formed Ministry of Health and Medical Education is responsible for every aspect of policy making, planning, leadership, stewardship, supervision and evaluation of health services, in addition to the training and educating of human resources for health, within the “Comprehensive Health Care Delivery System” that makes up Iran’s health infrastructure. From 1979 to 2020, the number of medical, dentistry and pharmacy schools have increased from 7 to 47, 3 to 35 and 3 to 22, respectively, with a rise in student yearly admissions in all programs of medical sciences from 1387 to 48120. There were no PhD or clinical subspecialty programs in 1979, whereas in 2020, annual student admission rates for such programs were 1038 and 219, respectively; these have been accompanied by marked improvements in the quality of education, clinical care and major health indicators such as increase in life expectancy, access to PHC in rural area, access to clean water, total number of rural health houses and vaccination coverage, on the other hand decrease in maternal, neonatal and under 5years mortality rates, decline in the number of patients sent abroad for treatment and also the number of foreign general physicians practicing in Iran..As a result ofsignificant rise in research activitiesthe number of scientific medical publications have increased from less than 2000 to over 70,000 yearly and Iran has achieved rank of 16 among all countries of the world in this regard.Conclusion: Integration of medical education into the health care system has been an appropriate and economical strategy for achieving health promotion and the key point for the improvement of medical education for better social accountability in the Islamic Republic of Iran.